Fiscal policy implementation in Azerbaijan before, during and after the oil boom - Khatai Aliyev; Ilkin Gasimov (Contemporary Economics, 2018)
This study reviews Azerbaijan's fiscal policy implementation and discusses its changes before, during and after the oil boom. Specifically, the period prior to 2005 is considered pre-boom, 2005-2014 is considered the oil boom and the years after 2014 are considered the post oil boom period. It is observed that the country's fiscal policy was only slightly expansionary prior to the oil boom but highly expansionary during the oil boom. However, such expansion has not been sustainable due to being financed mostly by direct transfers from State Oil Fund of the Republic of Azerbaijan (SOFAZ) and taxes on the oil industry. As a result, the post oil boom period is characterized by contraction in the form of sharply decreasing public expenditures and initiatives to increase tax revenues, at least by preventing tax evasion. The expectations for the upcoming years include maintaining a contractionary policy by both decreasing budget expenditures and increasing tax rates or tightening measures against tax evasion. This study helps understand the current and near-term future fiscal policy challenges in Azerbaijan.
Keywords: E62; H20; H50; H61; 330; Fiscal policy; budget expenditures; tax policy; oil boom; Azerbaijan